Characteristics of Soil Derived from Ultramafic Rocks for Extensification of Oil Palm in Langgikima, North Konawe, Southeast Sulawesi - Tufaila, M.; Sunarminto, Bambang Hendro; Shiddieq, DjaÂ’far; Syukur, Abdul (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2011)
Oil palm plantation in Langgikima was mostly grown in soils derived from ultramfic rocks which contain low productivity. Therefore, a study was required to determine the charac-teristics of soils evolved from ultramafic rocks evaluated from the aspects of soil formation and classification as well as land suitability for oil palm extensification. Soil observation in field had been carried out in locations of oil palm plantation with slope gradient < 15%, with ultramafic bedrocks (harzburgite, serpentinite, and olivine websterite). Soils from ultramafic rocks were characterized by almost acid to neutral soil reaction, poor nutrient content available (N, P, and K) and exchangeable base cations, with very low to low CEC, low to medium BS, and clay minerals dominated by goethite and magnetite. Soils from harzburgite and serpentinite rocks were classified as Acrustoxic Kanhaplustults while those from olivine websterite rocks were classified as Rhodic Kanhaplustalfs. Nowadays, soils from ultramafic rocks were unsuitable (N2) for oil palm with the very low level of available P as the main limiting factor. Therefore, efforts on soil management were necessary to be performed by adding suitable organic materials and fertilizers based on soil characteristics and crops needs.Keywords: soil characteristics, ultramafic rock, oil palm